ДОСЛІДЖЕННЯ ВПЛИВУ ТЕХНОЛОГІЧНОГО РОЗКИДУ ПАРАМЕТРІВ КОМПОНЕНТІВ НА ХАРАКТЕРИСТИКИ ДЖЕРЕЛА ЖИВЛЕННЯ З П'ЄЗОТРАНСФОРМАТОРОМ - Кривошей, Д.А. (Інститут електродинаміки НАН України, Київ, 2012)
The effect of components parameters technological accuracy on characteristics of power supply based on piezoelectric transformer is investigated with simulation in OrCAD software. The device operation in the worst case of parameters technological spread is analyzed with Monte Carlo method. References 2, figures 3.